Picker routing in rectangular mixed shelves warehouses. (July 2018) - Weidinger, Felix
Abstract: Scattered storage (also denoted as mixed shelves storage) is a warehousing strategy often found in business-to-consumer online retailing. Unit loads are broken down into single items that are spread throughout the warehouse, leading to multiple storage positions per stock keeping unit. This paper investigates the picker routing problem in a rectangular scattered storage warehouse, which differs from classical picker routing problems by being a combined selection and routing problem. A proof of NP-hardness in the strong sense is provided and suited solution procedures are presented. Additionally, the impact of the degree of scatter on the length of picking tours is investigated for differing levels of heterogeneity of the order lines, providing managerial insights on when scattered storage should or should not be applied.